The effects of commodity discoveries on small open economies: Empirical evidence from the Falkland Islands - Bruce Morley (Economies, 2019)
The aim of this study is to determine the effects of discovering oil on the performance of a small open economy, in this case the Falkland Islands. Using an event study approach and the return on one of the Falkland Islands' main companies, the results suggest that the discovery of oil has mostly had a positive effect on this company, which serves as a proxy for the Falkland Islands economy. In addition, using an EGARCH approach, there is evidence that the discovery of oil has reduced the volatility or risk of the company and therefore potentially the economy as a whole. However, when the oil price is added to the model, this tends to dominate the effect of the discovery.
Keywords: Q32; Q42; 330; event study; oil discovery; risk; stock price